The Reality of Administrative Delegation in Government Sector in the Kingdom of Saudi Arabia: Field Study on Trainees in Institute of Public Administration - Al-Mahi, Mohammed (The Arab Journal of Administration, 2021)
The research aims to identify the reality of the administrative delegation in the government sector in the Kingdom of Saudi Arabia among respondent trainees in Institute of Public Administration, and to examine potentially significant differences in the level of administrative delegation due the difference of gender, specialization, functional class, years of experience and Administrative level, the study used the descriptive and analytical approach and was use the questionnaire which included (26) Items on four axes: the reality of delegation, the organization obstacles and personal obstacles to delegation for The superior and the subordinate. Where the questionnaire was distributed (367) data were analyze by frequency percentages, mean, t-tests for one sample, and analysis of variance in one direction using SPSS. The study reveals that the level of delegation is above the middle and the obstacles President the most availability in the Saudi work environment; moreover, the results show no significant differences between while the (gender, years of experience, sector, and educational level). The study proposes working to strengthen the delegation behavior of superiors by training in the delegation and providing an effective database and information for delegation.